STRATEGI PELAYANAN IMPUS (IMIGRASI MASUK KAMPUS) TERHADAP PENDAPATAN NEGARA BUKAN PAJAK (PNBP) DI MASA PANDEMI COVID 19 PADA KANTOR IMIGRASI KELAS I TPI PADANG - Juni Munandar; Yulihasri Yulihasri (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to prove the right management strategy in supporting the increase in Immigration PNBP at the Class I Immigration office of TPI Padang. In this study, a sample was taken in the form of Immigration PNBP derived from the Travel Document of the Republic of Indonesia issued by the Class I Immigration office of TPI Padang from April 2020 to April 2022 and PNBP data generated through the Campus Entrance Immigration program. The analysis method used is descriptive quantitative, namely focusing attention on problems that occurred at the time the research was carried out (at present) or problems of an actual nature. Based on the tests conducted, it was found that the Class I Immigration Office of TPI Padang has the ability to change the potential into an achievement and a better achievement. So that the right policy direction to be implemented is to increase and enlarge the role of the Class I Immigration Office of TPI Padang in various activities in accordance with its capabilities as well as to expand participation and take advantage of various opportunities. In future development, the Class I Immigration Office of TPI Padang can use a role growth strategy but is carried out in stages according to the priority scale. And this strategy is supported by alternative opportunities to attract the sympathy of lecturers, employees and students even more by providing Excellent Service so that lecturers, employees and students get fast service, precise and efficient.